Corrosion at Sulphide Inclusions in Stainless Steel - Daud, A. R. (Universiti Putra Malaysia Press, 1996)
Auger analysis was performed using a high resolution scanning auger electron microscope and auger electron spectroscopy. Elemental auger contour maps for corroded sulphide inclusions in stainless steel were presented. It was found that the copper enriched-manganese sulphide inclusions were uniformly corroded, which might be due to CU2S deposition on the surface of corroding inclusions. In contrast, manganese sulphide inclusions containing less copper were non-uniformly attacked, resulting in the formation of deep microcrevices at their edges.